Mycale (Oxymycale) acerata Kirkpatrick 1907 - Göcke, Christian; Janussen, Dorte (Zenodo, 2013)
Mycale (Oxymycale) acerata Kirkpatrick, 1907 (Fig. 10 C) Mycale acerata Kirkpatrick, 1907: 280 –282, 1908: 36, pl. 20, fig. 1, pl. 24, fig. 10. Burton 1929: 430, 1934: 23, pl. 8, figs. 1–4. Koltun 1964: 33, pl. 5, figs. 1–7, 1976: 169. Boury-Esnault & Van Beveren 1982: 52–53, figs. 14f–i. Ríos et al. 2004: 110– 111, fig. 9. Synonymy: Mycale acerata var. minor Hentschel, 1914: 63 –64. Mycale acerata var. sphaerulosa Hentschel, 1914: 63. Material. 11 fragmentary specimens from station 048-1 (SMF 11800, 11848 grown together with a specimen of Myxilla asigmata , 11849, 11850, 11859–11865), the true number of specimens sampled cannot be reconstructed from the fragments; 602.1 m, 70° 23.94' S, 8° 19.14' W, 12.01.2008. Material examined for comparison: BMNH 1908.2.5.170, holotype, National Antarctic Expedition HMS “Discovery”, W.Q. 25.IX.03, 12 hole (243), described in Kirkpatrick (1908), wet specimen. Description. Massive, soft sponges, whitish in ethanol. Skeleton a plumose reticulation of anastomosing spicular-spongin fibres fanning out towards the surface. Basal fibres very thick, in older parts of the sponge body often the only remains after tissue has decayed. Thus the sponges show a very characteristic habit as a mixture of living and dead parts. Surface covered by a distinct reticular ectosome. Oxeas 550 to 950 µm long, palmate anisochelae 80 to 100 µm long. Remarks. This well-known and wide-spread species has been described and illustrated in detail by Kirkpatrick (1908), Koltun (1964) and Ríos et al . (2004). Our new specimens are in accordance with earlier descriptions. The typical growth form has been pictured by Kirkpatrick (1908) and Ríos (2006), and is even recognizable on underwater-photographs taken by ROV. Representatives of this species are the largest and also among the most abundant sponges sampled on SYSTCO I station 048-1, although the total number of specimens cannot be evaluated due to the fragmentary state of most specimens. As these sponges are both large and abundant, they very likely ...